Mitigation of Ionizing Radiation-induced Bone Marrow Suppression by p38 Inhibition and G-CSF Administration - Li, Deguan (2011)
P38/G-CSF/RADIATION/HEMATOPOIETIC SYSTEM: p38 mitogen-activated protein kinases (p38) has been shown to be activated in hematopoietic stem and progenitors cells after exposure to ionizing radiation (IR) and its activation has been implicated in bone marrow (BM) suppression under various pathological conditions. Therefore, in the present study we investigated whether inhibition of p38 activity alone with SB203580 (SB, a specific p38 inhibitor) or in combination with granulocyte colony-stimulating factor (G-CSF) can mitigate total body irradiation (TBI)-induced BM damage and lethality. Our results showed that p38 inhibition with SB had no significant effect on the 30-day survival rates of the mice exposed to 7.2 Gy TBI when it was used alone but increased the survival of the mice when it was combined with G-CSF. This combined effect may be attributable to a better preservation or stimulation of hematopoietic stem and progenitor cells, because BM cells from SB and G-CSF-treated mice produced more colony forming units-granulocyte-macrophage (CFUs-GM) and 4-week cobblestone area forming cells (CAFCs) than the cells from either SB or G-CSF-treated mice after TBI in a colony forming cell assay and a CAFC assay, respectively. These findings suggest that the combined therapy with SB and G-GSF is more effective in mitigating TBI-induced acute BM injury than either agent alone.